Buddha: A Very Short Introduction - Carrithers, Michael (New York Oxford University Press, 1996)
Guides the readers through the complex information that Buddhist texts give about the life and teaching of the Buddha. The author discusses the social and political background of India in the Buddha's time, and traces the development of his thought. He also assesses the rapid and widespread assimilation of Buddhism and its contemporary relevance.
Includes Index and Illustrations.
Keywords: Buddha